Pemberdayaan Perempuan melalui UMKM Berbasis Lingkungan dan Edukasi Kesehatan Reproduksi untuk Mewujudkan Generasi Gemilang Indonesia - Afrilia, Eka Mardiana (Yayasan Daarul Huda Kruengmane, 2025)
Women play a strategic role in nation building, both through their contribution to the economic sector and in giving birth to a healthy generation of successors. The KKN program of UMT d Karang Tengah District integrates eco-friendly SME training with reproductive health education as a form of women’s empowerment. Community empowerment through environmentally based Small and Medium Micro Enterprises (SMEs) constitutes one of the strategies in enhancing economic self-reliance while safeguarding nature’s sustainability. However, the sustainability of women SME actors’ enterprises is inextricably linked to their health conditions, particularly reproductive health. Muhammadiyah Tangerang University’s Integrated Real Work Tuition (RTL) program in Karang Tengah District aims to enhance women’s capacity through environment-based training of SMEs and reproductive health education. Methods include skills training, health extension, workshops, companionship, as well as formation of neighborhood-based enterprise groups. Results show there is an improvement in production and marketing skills of MSMEs, an increase in reproductive health knowledge (menstrual health, family planning, adolescent nutrition of girls and pregnant mothers), as well as the formation of a more holistic ecosystem of empowerment. increasing mothers’ skills in processing organic waste, increasing awareness of maintaining reproductive health, the formation of waste banks, as well as the growth of a group of eco-friendly SMEs integrated with reproductive health education. The program contributes to women’s empowerment, family economic strengthening, and the achievement of Indonesia’s glorious generation. The program asserts that reproductively healthy and economically empowered women are key to the creation of Indonesia’s golden generation.